Direct transformation of ReO3 nanorods into ReS2 nanosheets on carbon fibres for modulating solid–gas interactions. Issue 11 (23rd February 2022) - Lee, Song Hee; Kim, Noeul; Jeong, Ji Hwan; Kim, Bo-Hye; Yu, Hak Ki; Kim, Myung Hwa
Abstract : The gas adsorption/desorption reaction that occurs on a solid surface forms the basic reaction of various catalysts and sensor devices. Abstract : The gas adsorption/desorption reaction that occurs on a solid surface forms the basic reaction of various catalysts and sensor devices. If the phases of various solids can be easily controlled in a limited elemental composition, a highly efficient device may be realized through an in-depth understanding of the adsorption and desorption reactions of gases occurring on the surface of the solid. We thus report the direct phase transformation of ReO3 nanorods into 2-dimensional(2D) nanosheets of ReS2 on carbon fibres (CNFs) using a reducing heat treatment and induction of a sufurization reaction. The gas sensing abilities for NO2 and H2 were also explored in terms of the change of the electrical chracteristics for both 2D ReS2 nanosheets and ReO3 nanorods on CNFs.